Massive fetomaternal hemorrhage as a cause of severe fetal anemia - Dobrosavljević Aleksandar; Martić Jelena; Rakić Snežana; Pažin Vladimir; Janković-Ražnatović Svetlana; Srećković Svetlana; Dobrosavljević Branko (Vojnosanitetski Pregled)
Introduction. Fetomaternal hemorrhage (FMH) is a transfu-sion of fetal blood into the maternal circulation. A volume of transfused fetal blood required to cause severe, life-threatening fetal anemia, is not clearly defined. Some authors suggest vol-umes of 80 mL and 150 mL as a threshold which defines mas-sive FMH. Therefore, a rate of massive FMH is 1 : 1,000 and 1 : 5,000 births, respectively. Fetal and neonatal anemia is one of the most serious complications of the FMH. Clinical manifesta-tions of FMH are nonspecific, and mostly it presented as re-duced fetal movements and changes in cardiotocography (CTG). The standard for diagnosing FMH is Kleihaurer-Betke test. Case report. A 34-year-old gravida (G) 1, para (P) 1 was hospitalized due to uterine contractions at 39 weeks of gesta-tion. CTG monitoring revealed sinusoidal fetal heart rate and clinical examination showed complete cervical dilatation. Im-mediately after admission, the women delivered vaginally. Ap-gar scores were 1 and 2 at the first and fifth minute, respec-tively. Immediately baby was intubated and mechanical ventila-tion started. Initial analysis revealed pronounced acidosis and severe anemia. The patient received intravenous fluid therapy with sodium-bicarbonate as well as red cell transfusion. With all measures, the condition of the baby improved with normaliza-tion of hemoglobin level and blood pH. Kleihaurer-Betke test revealed the presence of fetal red cells in maternal circulation, equivalent to 531 mL blood loss. The level of maternal fetal hemoglobin (HbF) and elevated alpha fetoprotein also con-firmed the diagnosis of massive FMH. Conclusion. For the successful diagnosis and management of FMH direct commu-nication between the obstetrician and the pediatrician is neces-sary as presented in this report.